A Novel Score Combining Magnetic Resonance Spectroscopy Parameters and Systemic Immune-Inflammation Index Improves Prognosis Prediction in Non-Small Cell Lung Cancer Patients With Brain Metastases After Stereotactic Radiotherapy - Guo, Dong; Liu, Jiafeng; Li, Yanping; Chen, Qingqing; Zhao, Yunzheng; Guo, Xinwei; Zhu, Shuchai; Ji, Shengjun (Frontiers in Oncology, 2022)
Objective: The aim of this study was to evaluate the significance of combination of the magnetic resonance spectroscopy (MRS) parameters and systemic immune-inflammation (SII) in patients with brain metastases (BM) from non-small-cell lung cancer (NSCLC) treated with stereotactic radiotherapy. Methods: 118 NSCLC patients with BM who treated with stereotactic radiotherapy were retrospectively enrolled into this study. All patients underwent MRS and blood samples test for SII analysis before the initiation of stereotactic radiotherapy. The correlation between the parameters of MRS and SII level were assessed using the spearman correlation coefficient. The cut-off values for the parameters of MRS, SII and clinical laboratory variables were defined by the receiver operating characteristic (ROC) curve analysis to quantify these predictive value. The prognostic factors of overall survival (OS) and progression-free survival (PFS) curves were assessed using Kaplan-Meier and Cox proportional hazards models. Results: The median follow-up time was 25 months (range, 12-49months). The optimal cutoff point for the cho/cr and SII were 1.50 and 480, respectively. The cho/cr was negatively correlated with SII (rs = 0.164, P = 0.075), but there was a trend. C-SII score was established by combining cho/cr and SII. Patients with both an elevated cho/cr (> 1.50) and an elevated SII (> 480) were given a C-SII score of 2, and patients with one or neither were given a C-SII score of 1 or 0, respectively. Kaplan–Meier analysis showed that the C-SII score of 2 was significantly linked with poor OS and PFS (P < 0.001, P < 0.001). In the Cox proportional hazards model, the C-SII score independently predicted OS [hazard ratio (HR), 1.749; 95% CI, 1.176-2.601; P = 0.006] and PFS (HR, 2.472; 95% CI, 1.624-3.763; P < 0.001). Conclusion: C-SII score was more accurate for predicting the clinical outcomes of NSCLC patients with BM who undergo stereotactic radiotherapy. The C-SII score, which was superior to either score alone, which could be used to identify for BM from NSCLC patients with poor outcomes.